Analisis Penggunaan Fasilitas Masjid Dalam Pembelajaran Pendidikan Agama Islam di MAS Nahdhatul Islam Mancang Kecamatan Selesai Kabupaten Langkat - Pratiwi, Supia; Daulay, Mahmud Yunus (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research aims to analyze how the mosque functions as a facility in Islamic religious education which is located at the MAS Nahdhatul Islam Mancang School, Finish District, Langkat Regency. The focus of this research is how school management functions in the functioning of school mosques for the development of Islamic religious education, whether school management has provided implementation capable of developing mosques as a means for the development of Islamic religious education. In its implementation, researchers used descriptive analysis. The samples used were the principal of the Mas Nahdhatul Islam Mancang school, teachers and students of class VII MAS Nahdhatul Islam Mancang. Data collection was carried out by researchers in the form of observations, interviews, documentation taken when students were studying Islamic religion in the mosque and doing triangulation to find the validity of the data obtained. The results of the study show that the role and management carried out by teachers and schools in the functioning of mosques as the development of Islamic religious education is developing by filling in various additional activities such as learning tausyiah, memorizing the Koran, and tahsin training. With the efforts of school management and teachers' efforts to function mosques as the development of Islamic religious education, it can have a big impact on students at the school and especially in class VII aliyah. Apart from learning, the character of students is also formed to be more religious, more moral.